Pengembangan Karakter Kerja Keras Dan Hasil Belajar Pjok Materi Lompat Jauh Gaya Jongkok Melalui Penggunaan Bok Kardus Pada Siswa Kelas V SD 2 Kedungsari - Lukartono Lukartono (Universitas Muria Kudus, 2018)
In this study, researchers experienced problems in Long Jump learning, namely for elementary school students researching the use of cardboard tools to improve students' long jump learning outcomes, from pre-cycle to cycle I and from cycle I to cycle II. The learning process in pre-cycle has not used tools so students' learning outcomes are low. Increases occur in cycle I. Student learning outcomes increase even though not optimal. The implementation of cycle II causes student learning outcomes to increase to high so that they can support a quality learning, begin to become entrenched and through the use of cardboard media modification can improve learning outcomes of PJOK.